Implementasi Pembelajaran Peer Teaching Pada Mata Pelajaran Pendidikan Agama Islam di SMA Karya Ibu Palembang Sumatera Selatan - IKHWAN, MUNIRUL (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
The purpose of this study is to describe the activities of Islamic religious education and the implementation of peer teaching on PAI subject at SMA Karya Ibu Palembang. Therefore, this research is a descriptive study, the research that explores the description a symptom, specific activities with the data qualitatively. The data analysis used in this study is interactive model (data reduction, data display, data verification).The findings of the study showed that the school policy to the implementation of Islamic education is; that PAI subject was taught in SMA Karya Ibu with the time allocation 3 hours of subject per week. Two hours of subject was a core school hours, while the one-hour subject is a subject hours plus extra for religious programs. The implementation of peer teaching on PAI subject can be quite successful, but it still needs to be improved further. Because there are some things that need to be considered in order to improve the quality of learning, especially in PAI subject at SMA Karya Ibu Palembang in the future time.